2009
DOI: 10.1016/j.nima.2008.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Recent results on the properties of two-phase argon avalanche detectors

Abstract: The characteristic properties of two-phase Ar avalanche detectors, including those obtained with CsI photocathode, are further studied. Such detectors are relevant in the field of coherent neutrino-nucleus scattering and dark matter search experiments. The detectors investigated comprised a 1 cm thick liquid Ar layer followed by a triple-GEM multiplier. In these detectors, typical gains reaching 10 4 were obtained with good reproducibility and a stable operation for at least one day was demonstrated. Amplitude… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 17 publications
(25 reference statements)
3
33
1
Order By: Relevance
“…It was demonstrated that CsI coated GEMs, capillary plates as well as THGEMs have high quantum efficiencies at cryogenic temperatures for the UV photons and thus can replace expensive photomultipliers usually used in cryogenic TPCs for the detection of the scintillation light. Recently the Novosibirsk group confirmed our results obtained with CsI coated GEMs [61] using a double phase noble liquid detector (see Fig. 23).…”
Section: 21cryogenic Photodetectorssupporting
confidence: 77%
“…It was demonstrated that CsI coated GEMs, capillary plates as well as THGEMs have high quantum efficiencies at cryogenic temperatures for the UV photons and thus can replace expensive photomultipliers usually used in cryogenic TPCs for the detection of the scintillation light. Recently the Novosibirsk group confirmed our results obtained with CsI coated GEMs [61] using a double phase noble liquid detector (see Fig. 23).…”
Section: 21cryogenic Photodetectorssupporting
confidence: 77%
“…Recently the Novosibirsk group confirmed our results obtained with CsI coated GEMs [29] and also confirmed that a THGEM is a very robust detector capable of operating stably at cryogenic temperatures up to 78 K [23]. This group also investigated the operation of the old version of the screen-printed resistive GEM (described in [10]) and fully confirmed our results obtained with this detector at room temperature [23].…”
Section: B Test Oriented For Dark Matter Detectorssupporting
confidence: 79%
“…A triple-GEM structure with a CsI photocathode deposited on the bottom surface of the first GEM was tested in double-phase argon at 84 K and P = 0.7 bar [340,302]. Primary scintillation from 60 keV γ-rays was detected at a gain of 1.4·10 3 , however with surprisingly low efficiency (about 2 photoelectrons at the entrance of the first GEM).…”
Section: Photon Detection With Micro-pattern Structuresmentioning
confidence: 99%